Interfacial Adhesion between Thermal Spray Coating and Substrate Achieved by Ultrasonic Finishing - Kovalevskaya Zh. G. Zhanna Gennadievna (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen